Flume Tank Evaluation on the Effect of Liners on the Physical Performance of the Antarctic Krill Trawl - Hao Tang; Hao Tang; Hao Tang; Hao Tang; Bruno Thierry Nyatchouba Nsangue; Achille Njomoue Pandong; Pingguo He; Xu Liuxiong; Xu Liuxiong; Xu Liuxiong; Xu Liuxiong; Fuxiang Hu (Frontiers in Marine Science, 2022)
The Antarctic krill (Euphausia superba) is one of the most abundant resources in the ocean, which provides food for several important species in the Antarctic Ocean, and is targeted commercially by humans for many decades. To sustainably manage and harvest the species, energy-efficient, catch-efficient, and selective fishing gears should be developed for the Antarctic krill trawl fishery. This study investigates the effect of twine area and the liner length on the engineering performance of trawl through flume tank testing of trawl model to predict the performance of the full-scale midwater trawl used in the Antarctic krill fishery. Four 1/35th scale trawl model nets with varying lengths of the liner, based on the traditional trawl used in the Antarctic krill fishery, were designed using modified Tauti’s law and were tested in a flume tank at different towing speed, door spread, heavy bob weight, and the ratio of buoyancy to the fishing line (F/G). The results showed that the reduction in liner length by 25 and 50% from the traditional trawl net led to the decrease in twine area by 11.01 and 19.31% and, consequently, resulted in reductions in the lower bridle tension by 12.44 and 19.78%, and increases in energy efficiency by 17.98 and 25.73%, respectively. In addition, the reduction in liner length by 25 and 50% were found to increase the net mouth opening by 2.63 and 5.38% and the swept area by 6.52 and 8.38%, respectively, both of which are proportional to catch rates. Although the trawl net with 50% liner length is more energy-efficient and large mouth opening than those of the trawl net with the liner length over 75% of the trawl body, the large mesh section without a liner can result in the escape of the krill from the trawl, reducing overall catch efficiency. We, therefore, recommend the trawl with 75% of liner length as a suitable design for Antarctic krill considering energy efficiency and catch efficiency.